Literacy Barriers In Efforts To Develop Students' 21st-Century Skills - Rahmatiani, Lusiana; Darmawan, Cecep; Komalasari, Kokom; Rahmat, Rahmat (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
This study explores the obstacles in implementing literacy habituation programs at SMPN 1 Tempuran and their implications for the development of students’ 21st-century competencies, namely critical thinking, creativity, communication, and collaboration (4Cs). Employing a descriptive qualitative method, data were collected through observations, interviews, and documentation. The findings reveal that the literacy program, although structured through reading routines and digital resources, faces significant barriers such as inconsistent implementation, limited reading materials, low student motivation, and insufficient integration with collaborative learning. These issues hinder the development of higher-order thinking and communication skills. The study emphasizes the critical role of teachers as literacy facilitators and the need for contextual, reflective, and technology-integrated strategies to strengthen students’ competencies in a globalized digital era. This research further identifies three broad categories of obstacles: personal (low motivation and reading interest), institutional (limited integration of literacy into lessons, lack of relevant reading resources, and minimal teacher involvement), and socio-cultural (weak family and community support). The novelty of this study lies in its comprehensive mapping of literacy barriers within a multidimensional framework that connects structural, pedagogical, and cultural factors to the 4Cs, integrating perspectives from multiple stakeholders. The implications contribute to the development of more effective, inclusive, and future-oriented school literacy policies aimed at equipping students with the skills required to thrive in a global and digital society.